Establishment limitation of holm oak (Quercus ilex subsp. ballota (Desf.) Samp.) in a Mediterranean savanna — forest ecosystem - Smit, Christian; Díaz, Mario; Jansen, Patrick (Annals of Forest Science, 2009)
• Tree recruitment in Mediterranean savannas is generally hampered, in contrast with the original oak forests where these savannas are derived from. We asked whether this diﬀerence in recruitment success can be explained by diﬀerential post-dispersal survival. For one year we monitored experimentally cached holm oak acorns in a savanna – forest ecosystem in Central Spain, and recorded cache pilferage, type of pilferer, boar rooting, seedling emergence, seedling survival and the cause of mortality. • Cache pilferage was signiﬁcantly lower in savanna (8%) than in forest (21%). However, the higher cache survival was more than oﬀset by lower seedling emergence and, particularly, by nine times higher seedling mortality in savanna, mainly due to desiccation. Wild boar rooting did not diﬀer between experimental caches and controls without acorns, indicating that individual cached acorns do not trigger rooting activity. • Our results indicate that the diﬀerence in post-dispersal survival between savanna and forest is due to lower emergence and, primarily, higher seedling mortality in savanna, not to higher cache pilferage. Absence of safe sites such as shrubs, abundantly present in the forest, may well explain the lack of recruitment in the savanna. Management measures appear necessary for long-term persistence of Mediterranean savannas in general.
Keywords: Dehesa; seed predation; seedling establishment; tree recruitment

Establishment limitation of holm oak (Quercus ilex subsp. ballota (Desf.) Samp.) in a Mediterranean savanna — forest ecosystem - Smit, Christian; Díaz, Mario; Jansen, Patrick (Annals of Forest Science, 2009)
• Tree recruitment in Mediterranean savannas is generally hampered, in contrast with the original oak forests where these savannas are derived from. We asked whether this diﬀerence in recruitment success can be explained by diﬀerential post-dispersal survival. For one year we monitored experimentally cached holm oak acorns in a savanna – forest ecosystem in Central Spain, and recorded cache pilferage, type of pilferer, boar rooting, seedling emergence, seedling survival and the cause of mortality. • Cache pilferage was signiﬁcantly lower in savanna (8%) than in forest (21%). However, the higher cache survival was more than oﬀset by lower seedling emergence and, particularly, by nine times higher seedling mortality in savanna, mainly due to desiccation. Wild boar rooting did not diﬀer between experimental caches and controls without acorns, indicating that individual cached acorns do not trigger rooting activity. • Our results indicate that the diﬀerence in post-dispersal survival between savanna and forest is due to lower emergence and, primarily, higher seedling mortality in savanna, not to higher cache pilferage. Absence of safe sites such as shrubs, abundantly present in the forest, may well explain the lack of recruitment in the savanna. Management measures appear necessary for long-term persistence of Mediterranean savannas in general.
Keywords: Dehesa; seed predation; seedling establishment; tree recruitment